2017
DOI: 10.1039/c6gc03521c
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic radical-cascade cycloaddition of isocyanides, selenium and imidamides: facile access to 1,2,4-selenadiazoles under metal-free conditions

Abstract: A facile and novel method for the synthesis of functionalized 1,2,4-selenadiazoles through aerobic radical-cascade cyclization of isocyanides, selenium and imidamides is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…Isocyanides are the most reactive organic species in a panoply of molecules of interest in the chemical community. 11 Among them, multicomponent 12 cycloaddition, 13 annulation, 14 and radical reactions 15 have been extensively studied for the preparation of nitrogen-containing molecules, and natural and drug-like products with potential bioactivities. 16 Despite these research efforts, our research into green and sustainable protocols has continued, including visible light-based platforms 17 and isocyanide-mediated reactions.…”
mentioning
confidence: 99%
“…Isocyanides are the most reactive organic species in a panoply of molecules of interest in the chemical community. 11 Among them, multicomponent 12 cycloaddition, 13 annulation, 14 and radical reactions 15 have been extensively studied for the preparation of nitrogen-containing molecules, and natural and drug-like products with potential bioactivities. 16 Despite these research efforts, our research into green and sustainable protocols has continued, including visible light-based platforms 17 and isocyanide-mediated reactions.…”
mentioning
confidence: 99%
“…Subsequently, Ji and co‐workers expanded the application of isoselenocyanate intermediate to the synthesis of 1,2,4‐selenadiazoles through radical‐cascade cycloaddition of isocyanides, imidamides, and elemental selenium (Scheme 34). [67] The reaction was conducted using air as the green oxidant under metal‐free conditions, in which water served as the sole by‐product. Interestingly, control experiments suggested that TEMPO as a radical initiator could promote this radical‐cascade cyclization.…”
Section: Synthesis Of Organoselenium Compounds With Elemental Seleniummentioning
confidence: 99%
“…The synthesis of 1,2,3-thiadiazole derivatives 97 was reported by Li and Jiang using iodine as a SET catalyst ( Scheme 14F), 70 while an oxidative N-Se bond formation strategy for the synthesis of 1,2,4-selenadiazoles 98 was recently disclosed by Ji/Wang and co-workers ( Scheme 14G). 71 The reaction of isocyanides with selenium powder results in the corresponding isoselenocyanates 101, which undergo coupling with the amidines and oxidative cyclization, giving the selenadiazoles. Considering the lack of metal catalyst in this process, the role of oxygen was suggested to be related to the oxidation of the anionic organic intermediate 102 formed upon addition of the imidine to the isoselenocyanate, leading to a Se-centered radical (103).…”
Section: Oxidative N-o N-s and N-se Bond Formationmentioning
confidence: 99%